Colonial subjects : Puerto Ricans in a global perspective - Grosfoguel, Ramón (University of California Press, 2003)
Colonial Subjects is the first book to use a combination of world-system and postcolonial approaches to compare Puerto Rican migration with Caribbean migration to both the United States and Western Europe. Ramon Grosfoguel provides an alternative reading of the world-system approach to Puerto Rico's history, political economy, and urbanization processes.
Keywords: Puerto Ricans -- United States -- History -- 20th century.; Puerto Ricans -- Migrations -- History -- 20th century.; Puerto Ricans -- Europe -- History -- 20th century.; Puerto Rico -- Emigration and immigration -- History -- 20th century.; United States -- Emigration and immigration -- History -- 20th century.; Europe -- Emigration and immigration -- History -- 20th century.; Puerto Rico -- Colonial influence.; Puerto Rico -- Social conditions -- 1952-; Caribbean Area -- Colonial influence.; Portoricains -- Migrations -- Histoire -- 20e siècle.; Portoricains -- Europe -- Histoire -- 20e siècle.; Porto Rico -- Émigration et immigration -- Histoire -- 20e siècle.; Europe -- Émigration et immigration -- Histoire -- 20e siècle.; Porto Rico -- Influence coloniale.; Porto Rico -- Conditions sociales -- 1952-; Caraïbes (Région) -- Influence coloniale.; États-Unis -- Émigration et immigration -- Histoire -- 20e siècle.; 15.85 history of America.; SOCIAL SCIENCE -- Emigration & Immigration.; Colonial influence; Emigration and immigration; Puerto Ricans; Puerto Ricans -- Migrations; Social conditions; Caribbean Area; Europe; Puerto Rico; United States; Globalisierung; USA; Migratie (demografie); Puertoricanen.; Latino-Américains -- États-Unis.; Portoricains -- États-Unis -- Émigration et immigration.; Portoricains -- Europe de l'Ouest.; Porto Rico -- Emigration et immigration -- 20e siècle.; Caribbean Region -- Colonial influence.; Europe -- Emigration and immigration -- History -- 20th Century.; Puertoricaner.; Since 1900; History